PENERAPAN METODE LANGSUNG DALAM PEMBELAJARAN MENULIS BAHASA INDONESIA - Kausar; Abdul Haliq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to find out whether students' writing skills can be improved by using the direct method in learning writing in Indonesian. The method used in this research is literature review. This method was chosen given the limited time and adequate access to conduct fieldwork. Literature research allows the author to research relevant information and data from various reliable sources, including books, academic journals, and online articles. The results of this study show that the direct method plays a very important role in improving students' writing skills. The use of direct method in learning writing is an effective strategy to improve students' quality and interest. This method offers many benefits for students, both in terms of writing skills, and the development of critical and creative thinking skills. Therefore, the direct method is very suitable to be used in learning to write.